Selected psychological factors in elite male and female wrestlers - Rutkowska, K.; Gierczuk, D. (Journal of Combat Sports and Martial Arts, 2017)
Introduction. The study was designed to measure emotional intelligence of elite male and female wrestlers and to analyse their stress coping styles. Material and methods. A group of elite male and female wrestlers aged 18-26 years was studied. The psychological factors were analysed using two research tools: the Two-Dimensional Inventory of Emotional Intelligence (DINEMO) and the Coping Inventory for Stressful Situations (CISS). Results. The study participants achieved average scores for emotional intelligence and for particular stress-coping styles. Measurements of the selected psychological factors showed that male wrestlers and female wrestlers were significantly different from each other. The female wrestlers had a lower level of intrapersonal emotional intelligence. The male wrestlers had higher scores for the task-oriented style of coping with stress while the female athletes scored higher on the avoidance style. Conclusions. Emotional intelligence and stress-coping styles are among psychological factors that influence the functioning of male and female wrestlers in sport and personal life. A need has been identified to shape and develop their emotional intelligence and adaptive stress coping styles.